Creating a Competency-Based Medical Education Curriculum for Canadian Diagnostic Radiology Residency (Queen's Fundamental Innovations in Residency Education)-Part 2: Core of Discipline Stage. Issue 4 (November 2021) - Mishra, Siddharth; Chung, Andrew; Rogoza, Christina; Islam, Omar; Mussari, Benedetto; Wang, Xi; Dagnone, Damon; Cofie, Nicholas; Dalgarno, Nancy; Kwan, Benjamin Y. M.
Purpose: All postgraduate residency programs in Canada are transitioning to a competency-based medical education (CBME) model divided into 4 stages of training. Queen's University has been the first Canadian institution to mandate transitioning to CBME across all residency programs, including Diagnostic Radiology. This study describes the implementation of CBME with a focus on the third developmental stage, Core of Discipline, in the Diagnostic Radiology residency program at Queen's University. We describe strategies applied and challenges encountered during the adoption and implementation process in order to inform the development of other CBME residency programs in Diagnostic Radiology. Methods: At Queen's University, the Core of Discipline stage was developed using the Royal College of Physicians and Surgeons of Canada's (RCPSC) competence continuum guidelines and the CanMEDS framework to create radiology-specific entrustable professional activities (EPAs) and milestones for assessment. New committees, administrative positions, and assessment strategies were created to develop these assessment guidelines. Currently, 2 cohorts of residents (n = 6) are enrolled in the Core of Discipline stage. Results: EPAs, milestones, and methods of evaluation for the Core of Discipline stage are described. Opportunities during implementation included tracking progress toward educational objectives and increased mentorship. Challenges included difficulty meeting procedural volume requirements, inconsistent procedural tracking, improving feedback mechanisms, and administrative burden. Conclusion: The transition to a competency-based curriculum in an academic Diagnostic Radiology residency program is significantly resource and time intensive. This report describes challenges faced in developing the Core of Discipline stage and potential solutions to facilitate this process.